2021
DOI: 10.55599/ejssm.v6i7.34
|View full text |Cite
|
Sign up to set email alerts
|

Radar-Based Assessment of the Detectability of Giant Hail

Abstract: The occurrence of giant hail, defined as hail ≥102 mm (4.00 in) in diameter, is a relatively rare phenomenon, accounting for less than 1% of all hail reports in the United States.  Despite the infrequent nature of these events, hail of this magnitude has the potential to cause extreme damage to property and a substantial threat to exposed life.  The short-term prediction of these events has been challenging.  For giant hail since 2005, only 7% of convective warnings and severe-weather statements issued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Previous studies have used data from the SED to analyze the reporting of other various weather phenomena (Ashley & Black, 2008 ; Bentley et al., 2002 ; Dixon et al., 2005 ; Markowski et al., 1998 ). Many found the SED to be an inconsistent and inaccurate record of severe weather (Ashley & Black, 2008 ; Ashley & Gilson, 2009 ; Black & Ashley, 2010 ; Black & Mote, 2015 ; Blair et al., 2011 ; Downton et al., 2005 ; Miller et al., 2016 ; Trapp et al., 2006 ). Others also found the reports on damage, injuries, and fatalities to be incomplete and inconsistent (López et al., 1993 ; Santos, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have used data from the SED to analyze the reporting of other various weather phenomena (Ashley & Black, 2008 ; Bentley et al., 2002 ; Dixon et al., 2005 ; Markowski et al., 1998 ). Many found the SED to be an inconsistent and inaccurate record of severe weather (Ashley & Black, 2008 ; Ashley & Gilson, 2009 ; Black & Ashley, 2010 ; Black & Mote, 2015 ; Blair et al., 2011 ; Downton et al., 2005 ; Miller et al., 2016 ; Trapp et al., 2006 ). Others also found the reports on damage, injuries, and fatalities to be incomplete and inconsistent (López et al., 1993 ; Santos, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In subtropical South America, the majority of significant hailstorms are not from discrete storms, such as isolated supercells, but rather from organized multicell convection (Bruick et al., 2019). In contrast, the majority of hailstorms producing hail in excess of 5 cm have been found to be associated with supercells in the United States (Blair et al., 2011; Grams et al., 2012; B. T. Smith et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Those authors found significant underprediction of hail size both in National Weather Service warnings and Storm Prediction Center watches for these giant hail cases. Similarly, Blair et al (2017) found that severe thunderstorm warnings tended to underestimate hail size for severe (.2.5 cm) and significantly severe (.5.0 cm) hail, and that the maximum hail size officially reported in the Storm Data database tended to be considerably lower than what was actually observed. Thus, a better understanding of storms that produce very large and potentially damaging hail is needed to improve our ability to forecast, detect, and warn for these hazards, and ultimately mitigate damages to property or life.…”
Section: Introductionmentioning
confidence: 80%